2012
DOI: 10.1007/s10461-012-0333-8
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Acceptability in MTN 001: A Randomized Cross-Over Trial of Daily Oral and Topical Tenofovir for HIV Prevention in Women

Abstract: We compared adherence to and acceptability of daily topical and oral formulations of tenofovir (TFV) used as pre-exposure prophylaxis (PrEP) for HIV prevention among women in South Africa, Uganda and the United States. 144 sexually active, HIV-uninfected women participated in a cross-over study of three regimens: oral tablet, vaginal gel, or both. We tested for differences in adherence and evaluated product acceptability. Self-reported adherence for all regimens was high (94%), but serum TFV concentrations ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 21 publications
6
60
1
Order By: Relevance
“…These findings are consistent with perspectives of the US women enrolled in an open-label cross-over trial of oral and topical PrEP in which a greater proportion of US women as compared to African women preferred oral PrEP to topical PrEP. 29 These results are also consistent with studies of women's product preferences for contraception, in which women were more accepting of oral contraceptives than of topical contraceptives, without counseling from a provider. 42 One Indian study noted that women preferred an oral formulation of PrEP because of their perception that it offered greater potential for undisclosed use.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These findings are consistent with perspectives of the US women enrolled in an open-label cross-over trial of oral and topical PrEP in which a greater proportion of US women as compared to African women preferred oral PrEP to topical PrEP. 29 These results are also consistent with studies of women's product preferences for contraception, in which women were more accepting of oral contraceptives than of topical contraceptives, without counseling from a provider. 42 One Indian study noted that women preferred an oral formulation of PrEP because of their perception that it offered greater potential for undisclosed use.…”
Section: Discussionsupporting
confidence: 84%
“…Although studies have assessed PrEP acceptability among men who have sex with men, 21,22 men and women in international settings, [23][24][25][26] and high risk heterosexuals in the US, 27,28 there is a critical need to understand PrEP acceptability and product preferences among US black women, [29][30][31][32] given the high HIV incidence in this population. A national survey of adult women in the US found that African American women were more likely than white women to consider using oral PrEP and that cost, peer perspectives, and physician input would influence their decision making.…”
mentioning
confidence: 99%
“…[51] Other studies of hypothetical use among people not participating in trials have reported willingness to use oral PrEP among young urban African American men and women,[52] although a substantial proportion (40%) of male and female emergency room patients in two New York City hospitals indicated that they were unlikely to use it. [53] Among female sex workers in China, willingness to use PrEP correlated with interpersonal factors, such as level of trust in physicians.…”
Section: Interventions For Preventing Hiv Infection Among Womenmentioning
confidence: 99%
“…Preferences for vaginal gel versus tablets for PrEP, for example, varied somewhat among clinical trial participants by region, with US women preferring tablets, while African women were divided in their preference for gel or tablets. [51] The study's authors note that a potential advantage of a gel over a pill or condom is that the increased lubrication afforded by the gel may allow its promotion as a sexual health benefit that improves sex and partner satisfaction rather than simply as a disease prevention device that may raise questions of infidelity. [51] Further research is needed to better define the efficacy of PrEP in women, identify new drugs for PrEP, and enhance adherence to this intervention.…”
Section: Interventions For Preventing Hiv Infection Among Womenmentioning
confidence: 99%
“…In a PrEP trial with sexually active, HIV-infected individuals in South Africa, Uganda, and the U.S., the acceptability of oral PrEP tablets, vaginal PrEP gels, or both were examined [52]. Across sites, oral PrEP, if found to be effective, was the most acceptable mode of administration [52].…”
Section: Introductionmentioning
confidence: 99%